PENGARUH CITRA DESTINASI, NILAI PELANGGAN TERHADAP KEPUASAN WISATAWAN DAN NIAT BERPERILAKU WISATAWAN - Sitanggang, Dicky Andrew; Sunarti, Sunarti; Pangestuti, Edriana (FIA UB, 2020)
The purpose of this study is to present a conceptual model between Destination Image, Customer Value, Tourist Satisfaction and Tourist Behavioral Intention. Based on theoritical and empirical study about destination image, tourist value, tourist satisfaction and tourist behavioral intention, this study explain the constructs and relationships between variables that are used as a basis in constructing conceptual models. Based on previous studies, the authors develop a proposition where a destination with a positive image will be more likely to create tourist satisfaction and positive behavioral intention. In addition, giving value to tourists is also considered as an antecedent of tourist satisfaction and tourist positive behavioral intention. In the end, tourists who are satisfied with the destination will have positive behavioral intentions. Thus, further studies are expected to discuss the variables in this study, as well as develop estimates of other variables that can influence or increase by the variables that have been discussed in this study in the tourism sector, specially in Indonesia.